The Demonstration and Audiovisual Health Education Package (Demavi) Could Affect the Housewives’ Knowledge of First-Aid in Burns - Nutrisia Nu'im Haiya; Iwan Ardian; Siti Marfu'ah (Universitas Airlangga, 2020)
Introduction: Burns is a condition that is experienced by the community that can cause skin damage to the epidermis. This is often experienced by housewives due to their daily life in the kitchen. So that this does not cause serious problems, then housewives need sufficient knowledge. The use of demonstration and audiovisual (Demavi) health education is packaged to increase one's knowledge. The study aims to recognize the impact of the demonstration health education package and audiovisual on the first aid knowledge of the burns on housewives in Bangetayu WetanMethods: This type of research is quantitative research. The design used a quasi-experiment with the control group pretest-posttest. The instrument used in this study was a questionnaire with 27 closed-ended questions with multiple choice answer. The number of respondents is 107 which are 54 in treatment group and 53 in control group using the simple random sampling. Data obtained are statistically processed using chi-square testResults: The result of the statistical test shows significant effects of demonstrations and audiovisual and health education packages on knowledge about first aid burns among housewives with p-value of 0.094.Conclusion: The demonstration and audiovisual health education packages has an effect on housewives’ knowledge of first aid in burns. Other package methods can be developed to make it easier for health workers to do health promotion, and other methods of health promotion package development should be adapted to the theme of the material and the existing audience characteristic.